Principle of Cooperation in Human Conversation - Risma Sari; Suci Chairunnisa; Kristina Gultom; Ega Sauly Sitio (JELITA, 2020)
In communication, each party involved, namely between the speaker and the speech partner, will always try to convey his speech effectively and efficiently. Grice mentioned that a reasonable discourse could occur if the speaker and hearer are compliant with the principle of cooperative communication. This study aims to explain what it is called maxims in human conversation. The data in this qualitative study were taken from 5 prominent articles which explain and review the theory. This research uses a descriptive qualitative form to analyze and describe the words or sentences used in defining the theory proposed by Grice. The results of this study, in brief, mentioned the principle of cooperation in conversation consists of four conversational maxims, namely: Maxim of quantity, Maxim of quality, Maxim of Relevance and Maxim of implementation.